Pragmatic Study: Types And Functions Of Speech Acts In Pooh's Dialogue In "Winnie The Pooh" - Wasan Khalid Ahmed; Alma Cita Calimbo; Le Thi Giao Chi (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: The purpose of this study is to analyze the types of speech acts used by the character Pooh in the dialogue of the Winnie the Pooh story. This study aims to identify locution, illocution, and perlocution in Pooh's utterances and to understand the functions and effects of the communication produced. Methodology: This study uses a qualitative method with a content analysis approach. Data in the form of Pooh character utterances in Winnie the Pooh were analyzed based on John Searle and J.L. Austin's speech act theory. Data collection techniques were carried out through documentation, with samples selected using purposive sampling. Data analysis refers to the Krippendorff content analysis method. Main Findings: This study found that Pooh used 258 speech acts in 90 dialogues, consisting of locution, illocution, and perlocution. The most dominant illocutionary act was representative (49.6%), while perlocutionary acts were most often used to convince the listener (58.1%). Pooh used more direct speech acts (235 times) than indirect (23 times), indicating a tendency towards more explicit communication in interactions. Novelty/Originality of this study: This study provides a new perspective in the analysis of speech acts in children's literature, especially Winnie the Pooh. This study reveals the communication patterns of Pooh characters that have not been widely studied, as well as their contribution to understanding language strategies in literary texts. These findings can enrich pragmatic studies and support children's literacy-based language learning.